Full wolf moon [compact disc, unabridged] : a novel - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2017)
A new thriller that follows the trail of a killer who cannot exist ... featuring Jeremy Logan, the renowned investigator of the supernatural and fantastic.